Autoimmune metaplastic atrophic gastritis in chinese: a study of 320 patients at a large tertiary medical center. (1st February 2017) - Zhang, Hejun; Jin, Zhu; Cui, Rongli; Ding, Shigang; Huang, Yonghui; Zhou, Liya
Abstract: Objectives: Autoimmune metaplastic atrophic gastritis (AMAG) is an uncommon disease worldwide and may predispose to gastric carcinoid tumors or adenocarcinomas. The aims of this study were to outline the clinical characteristics of Chinese AMAG patients, including demographic pattern, hematologic features, and gastroscopic and histopathologic findings. Patients and methods: A total of 320 Chinese patients with AMAG, from January 2007 to December 2014, were reviewed in a regional hospital of China. Results: Of the 320 AMAG patients, the mean age was 60.6 ± 12.3 years [range 26–86; 206 (64.4%) women]. The coarse annual detection rate was 0.9%. Anemia was present in only 19.3% patients (53/275) and 3.5% (11/315) AMAG patients also had primary biliary cirrhosis. One hundred and thirty-six had endoscopically identifiable lesions. These lesions consisted of 130 polypoid lesions (63 hyperplastic polyps, 2 oxyntic mucosa pseudopolyps, 2 intestinal-type gastric adenomas, 2 fundic gland polyps, 5 concurrent polyps, 14 well-differentiated neuroendocrine neoplasms, 7 submucosal tumors and 35 chronic gastritis), 6 adenocarcinomas. The detection rate of atrophy and intestinal metaplasia in antral mucosa were 47.2 and 37.5%, respectively. Conclusions: AMAG is more frequent than expected in China and display a female predominance, accompanied with other autoimmune disorders. AMAG should be paid more attention by clinicians through a multidisciplinary team approach.